Improved growth and cardiovascular risk after late steroid withdrawal: 2-year results of a prospective, randomised trial in paediatric renal transplantation - Höcker, Britta; Weber, Lutz T.; Feneberg, Reinhard; Drube, Jens; John, Ulrike; Fehrenbach, Henry; Pohl, Martin; Zimmering, Miriam; Fründ, Stefan; Klaus, Günter; Wühl, Elke; Tönshoff, Burkhard (Nephrology, dialysis, transplantation, 2010)
Background. Long-term corticosteroid treatment impairs growth and increases cardiovascular risk factors. Hence, steroid withdrawal constitutes a major topic in paediatric renal transplantation and maintenance immunosuppression. Methods. The lack of data from randomised controlled trials caused us to conduct the first prospective, randomised, multicentre study on late steroid withdrawal among paediatric kidney allograft recipients treated with standard-dose cyclosporine microemulsion (CsA) and mycophenolate mofetil (MMF) for 2 years. Forty-two low- or regular-immunologic risk patients were randomly assigned, ≥1 year post-transplant, to continue taking or to withdraw steroids over 3 months. Results. Two years after steroid withdrawal, they showed a longitudinal growth superior to controls [mean height standard deviation score (SDS) gain, 0.6 ± 0.1 SDS versus −0.2 ± 0.1 SDS ( P < 0.001)]. The prevalence of the metabolic syndrome declined significantly ( P < 0.05), 2 years after steroid withdrawal, from 39% (9/23) to 6% (1/16). Steroid-free patients had less frequent arterial hypertension (50% versus 93% ( P < 0.05)) and required fewer antihypertensive drugs [0.6 ± 0.2 versus 1.5 ± 0.3 ( P < 0.05 versus control)]. Additionally, they had a significantly improved carbohydrate and lipid metabolism with fewer hypercholesterolaemia and hypertriglyceridaemia ( P < 0.05 versus control). Patient and graft survival amounted to 100%. Allograft function remained stable 2 years after steroid withdrawal. The incidence of acute rejections was similar in the steroid-withdrawal group (1/23, 4%) and controls (2/19, 11%). Conclusion. Late steroid withdrawal in selected CsA- and MMF-treated paediatric kidney transplant recipients improves growth, mitigates cardiovascular risk factors and reduces the prevalence of the metabolic syndrome, at no increased risk of acute rejection or unstable graft function.